SOSIALISASI PENANGANAN KERUSAKAN KOMPONEN KAYU AKIBAT SERANGAN RAYAP DI DAERAH PERUMAHAN GRIYA MADANI KECAMATAN SIANTAR SITALASARI - Meylida Nurrachmania; Rozalina Rozalina; Marulam MT Simarmata; Tri Astuti; Tioner Purba (Universitas, 2022)
Economic losses due to wood damage by wood destruction factors in buildings in Indonesia have reached billions of rupiah every year. Surveys in several major cities, Jakarta, Surabaya, Bandung and other major cities show that generally residential buildings are particularly vulnerable to being attacked by wood-destroying organisms. To prevent or reduce economic losses due to wood damage by wood destruction factors in buildings especially housing, it is necessary to take a preventive measure that is a preservation measure by providing preservatives, especially on wood materials as well as handling to overcome wood components that have been damaged.